Labor insertion and employability university graduates from the Central Macro Region of Peru - Palomino-Crispín, Antonio E. (2021)
Objective. Was to determine the level of labor insertion of university graduates from the Macro Region of Central Peru. Method. The design was non-experimental; the research level was descriptive; The instrument used was the Labor Insertion questionnaire for university administration graduates, developed based on the perspective of Gómez-Cartolín (2015) which had 27 items, the dimensions were employability (with 15 items), and the employability dimension (12 items), the sample consisted of 315 university graduates from the Central Macro Region of Peru. Results. In the Junín region, 21.9% were men, and 22.5% were women; in Pasco 7.0% were men and 19.7% were women; In Huánuco 4.4% were men and 24.4% were women, making a total of 33.3% men and 66.7% women in the regions that make up the Central Macro Region of Peru. Conclusion. Labor insertion of the administration graduates of the Central Macro Region of Peru was medium, which indicates that they are working in activities related to their professional career, predominantly financial organizations.